Towards Sustainable Waste Management: A Study of Household Solid Waste Generation in Koya City - Anwer Hazim Dawood; Salah Farhan A. Sharif (Emerging Technologies and Engineering Journal)
Solid waste management (SWM) is an increasing challenge in Koya and its surrounding areas, driven by population growth and changing consumption patterns. This study assesses the current state of household solid waste (SW) generation and composition in the Koya District. A field survey was conducted across selected neighborhoods in Koya City to estimate household waste generation rates and analyze waste composition. The findings were compared with Koya Municipality records and showed strong consistency. The results indicate an average household waste generation rate of 1.035 kg/person/day in Koya City, with lower and higher rates observed in the Ashti (0.73 kg/person/day) and Shoresh (1.21 kg/person/day) districts, respectively. Composition analysis revealed that daily household waste is approximately 121 tons, predominantly composed of decomposable organic materials and paper, plastics, metals, glass, textiles, and dust. All household solid waste is disposed of in landfills without any reduction, reuse, or recycling practices. These findings highlight the urgent need for integrated SWM strategies in Koya to minimize environmental impacts and promote sustainable waste management.